2014
DOI: 10.1007/s10843-014-0136-2
|View full text |Cite
|
Sign up to set email alerts
|

Convergence in the priorities of entrepreneurial values: Empirical evidence from Malaysia

Abstract: This study aims to contribute to the field of international entrepreneurship by investigating entrepreneurial values priorities of Malaysian entrepreneurs compared to Western entrepreneurs and whether the magnitude of each entrepreneurial value is the J Int Entrep Summary highlights 1. Contributions: This study adopts and adapts Values Theory to study entrepreneurial motivations, which is an important aspect of the entrepreneurial process but under-researched. In addition, samples drawn from a collectivistic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The first school of thought suggests universality of entrepreneurial values. For example, Holt (1997) and Looi and Kamarulzaman (2015) found that the fundamental entrepreneurial values transcend national borders. Bruton et al (2008) noted that many entrepreneurship studies assume that entrepreneurs think and act similarly irrespective of cultural and institutional contexts of different countries.…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…The first school of thought suggests universality of entrepreneurial values. For example, Holt (1997) and Looi and Kamarulzaman (2015) found that the fundamental entrepreneurial values transcend national borders. Bruton et al (2008) noted that many entrepreneurship studies assume that entrepreneurs think and act similarly irrespective of cultural and institutional contexts of different countries.…”
Section: Review Of Literaturementioning
confidence: 99%
“…However, there is competing theory or alternative explanation (Cuervo-Cazurra et al, 2016; Terjesen et al, 2016; Zahra, 2007) of entrepreneurial intention. Prior studies found that the following demographic variables influenced entrepreneurial intention: (a) gender (Arenius & Minniti, 2005; Crant, 1996; Katz, 1992; Looi & Khoo-Lattimore, 2015; Matthews & Moser, 1996; Naffziger et al, 1994; Shook et al, 2003; Terjesen et al, 2016; Wennekers, Uhlaner, & Thurik, 2002; Wilson, Kickul, & Marlino, 2007); (b) family business background (Arenius & Minniti, 2005; Audretsch et al, 2002; Crant, 1996; Dubard-Barbosa, 2014; Katz, 1992; Kolvereid, 1996; Looi & Khoo-Lattimore, 2015; Matthews & Moser, 1996; Naffziger et al, 1994; Terjesen et al, 2016); and (c) education (Shook et al, 2003) or entrepreneurship education (Bae et al, 2014). These three variables are labelled as demographic control variables hereinafter.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, one unexpected positive life event arising from this pandemic is that learners may become better at self-regulation. This may cultivate their self-direction values, which is essential for entrepreneurship and intrapreneurship (i.e., entrepreneurial mindsets and behaviours) [46][47][48]. Moreover, the challenging experiences (i.e., adversity) of ERL may facilitate learners' positive adaptation of resilience for future challenges [49].…”
Section: Discussionmentioning
confidence: 99%
“…Openness to change may also entail lower propensity towards making decisions that support environmental sustainability, given a reduced focus on others (Grebitus, Steiner, & Veeman, 2013). These examples do not suggest that openness to change consistently leads to negative organisational behaviour, as entrepreneurs are often motivated by the self-direction component of openness to change (Looi & Kamarulzaman, 2015).…”
Section: Values and Organisational Behaviourmentioning
confidence: 99%